New Viscometers for Measuring the Viscosity of Liquids - Jamshidbek Shamuratov; Oybek Mustafayev; Islom Kadirov (Journal of Engineering)
This article’s goal is to present a viscometer that makes use of a novel viscometry measurement technique. The post will also suggest brand-new vibration viscometers. The development of new viscometers has allowed for the continuous and instantaneous measurement of liquid viscosity. The viscosity can be precisely measured automatically using these viscometers, which are made for industrial application. These viscosity measurement tools can currently be applied to a number of different tasks, including the research of recently developed oil products, the choice of the best flow characteristics for different transfer situations, and the advancement and refinement of fuel preparation techniques.